(untitled) (Bangladesh Journal of Agricultural Research, 2009)
The experiments were carried out at the Regional Agricultural Research Station, Rahmatpur, Barisal during the rabi seasons of 2001-2002 and 2002-2003 to study the impact of different sulphur levels on bulb yield, storability and economic return of onion. Sulphur application had significant effect on yield components and bulb yield of onion. The highest bulb yields (19.75 and 19.88 t/ha) were obtained from sulphur levels between 60 and 75 kg/ha in two consecutive years. Both the cumulative weight and rotten loss were significantly influenced by sulphur fertilization. The maximum weight loss (40.78%) was recorded after 180 days of storage in S60 kg/ha and the minimum (31.40%) was found in S45 kg/ha. The bulbs stored in bamboo platform were found in acceptable condition after 6 months of storage showing 31.40% of weight loss. The maximum rotten bulbs (63.75%) were observed in control treatment (without S) and the minimum rotten bulbs (37.04%) were observed in S45 kg/ha after 180 days of storage because application of sulphur enhanced the storability of onion bulbs. The highest (9146 %) marginal rate of return (MRR) with gross margin of Tk. 181844/ha was obtained from the sulphur level S60 kg/ha. Key Words: Sulphur, yield, storability, economic return, onion. doi: 10.3329/bjar.v33i4.2286 Bangladesh J. Agril. Res. 33(4) : 539-548, December 2008